2021
DOI: 10.1007/s00402-020-03739-2
|View full text |Cite
|
Sign up to set email alerts
|

Does early surgery improve outcomes for periprosthetic fractures of the hip and knee? A systematic review and meta-analysis

Abstract: Introduction Previous evidence has established that early surgery is beneficial to improve outcomes for individuals with native hip fractures in the elderly population. Patients who sustain a periprosthetic fracture have been demonstrated to have similar demographics and outcomes as those with native fractures around the hip and knee. We therefore set out to determine if there is a similar difference in perioperative outcomes between early and delayed surgery for periprosthetic fractures of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…The longest waits were observed in hip B2/3 type PPFs, in which the majority of patients underwent revision. A recent systematic review by Farrow et al 15 reported a mean time to surgery of 2.7 days, and observed that delays in surgery were associated with higher mortality and poorer clinical outcomes, including greater risk of medical complications, longer length of stay, higher transfusion risk, and increased rates of reoperation. Griffiths et al 10 reported that a delay to surgery of greater than 72 hours led to increased risk of postoperative complications, whereas Bliemel et al 16 observed that early surgery had no effect on mortality and patient outcomes at 120 days, but did find that the risk of reoperation was significantly higher in patients whose surgery was delayed.…”
Section: Discussionmentioning
confidence: 99%
“…The longest waits were observed in hip B2/3 type PPFs, in which the majority of patients underwent revision. A recent systematic review by Farrow et al 15 reported a mean time to surgery of 2.7 days, and observed that delays in surgery were associated with higher mortality and poorer clinical outcomes, including greater risk of medical complications, longer length of stay, higher transfusion risk, and increased rates of reoperation. Griffiths et al 10 reported that a delay to surgery of greater than 72 hours led to increased risk of postoperative complications, whereas Bliemel et al 16 observed that early surgery had no effect on mortality and patient outcomes at 120 days, but did find that the risk of reoperation was significantly higher in patients whose surgery was delayed.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies focusing on mortality in patients with PFF suggested different time intervals to separate early from delayed surgical treatment, e.g., 24 h [ 17 , 22 , 23 ] or 72 h [ 15 , 24 ]. A separate analysis of ATR-DGU using 24 and 72 h as cutoffs also failed to prove differences in regard to mortality (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical waiting times vary and there is some evidence that longer waiting times are associated with poorer outcomes, such as increased rates of transfusion, LOS, and mortality. 26,27 Revision surgery is more complex than ORIF and this explains the higher blood transfusion and critical care requirements observed in this group. The mean LOS was similar in the two groups, which was an unexpected finding as revision femoral components allow full weightbearing postoperatively whereas some surgeons may restrict weightbearing following ORIF.…”
Section: Discussionmentioning
confidence: 99%